PENGARUH WORK STRESS TERHADAP TURNOVER INTENTION DENGAN WORK ENGAGEMENT SEBAGAI VARIABEL MEDIASI - Novitaswara, Della; Rozaq, Khoirur (Universitas Negeri Surabaya, 2025)
This study aims to determine and analyze the effect of work stress on turnover intention with work engagement as a mediating variable. This research is a causal research with a quantitative approach. The population in this study amounted to 130 employees. The sampling technique used is non probability sampling technique, namely saturated sample technique. The statistical analysis method in this study is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) supported by SmartPLS 4.0.9 computer software. The results of this study indicate that there is a positive and significant effect of work stress on turnover intention, a negative and significant effect of work stress on work engagement, a negative and significant effect of work engagement on turnover intention, and work engagement can significantly mediate work stress on turnover intention. Therefore, Companies that want to reduce turnover intention need to pay more attention to work stress through work engagement.